Development and performance assessment of LPG operated cluster Porous Radiant Burner for commercial cooking and industrial applications. (15th March 2021) - Deb, Sunita; Muthukumar, P.
Abstract: A Cluster Porous Radiant Burner (CPRB) consisting of 3 individual burners of 70 mm diameter was developed and tested for its performance improvement over a single Porous Radiant Burner (PRB) of diameter 120 mm. Experiments were conducted for a firing rate of 12.6 kW following the guidelines given in BIS 14612:1999. The system used air at 1.5 bar as oxidizer and LPG as fuel. Within the range of stable equivalence ratios, the surface temperature distribution was analysed for ensuring uniform heat flux. Variations in thermal efficiency and CO and NOx emissions were analysed for different equivalence ratios. Experimental results suggest that the performances of a PRB can be improved when smaller diameter PRBs, with equivalent top surface area as that of a single-PRB, are clustered. Thereafter, in an endeavour to obtain an optimized size of the CPRB for maximum thermal performance, two more CPRBs with burner diameters of 80 mm and 90 mm were fabricated. Comparisons of the thermal performances of the CPRBs were made with Conventional Burners (CBs). Within the equivalence ratio of 0.7–0.85, maximum thermal efficiency improvement of 13.8% and 27% over a single-PRB and CB, respectively was attained with 80 mm CPRB. Graphical abstract: Image 1 Highlights: Performance study on Cluster Porous Radiant Burner (CPRB) has been presented. CPRB provides more uniform heat flux over a single- Porous Radiant Burner (PRB). CPRB yields maximum of ∼14% improved thermal efficiency (ηth ) over single-PRB. CPRB yields maximum of ∼27% improved ηth over conventional burners (CB). CPRB results in 85% and 83% reduction of CO and NOx respectively, compared to CB.